2011
DOI: 10.1371/journal.pone.0028631
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Quality of Care of Elderly Patients Using the ACOVE Quality Indicator Set: A Systematic Review

Abstract: BackgroundCare of the elderly is recognized as an increasingly important segment of health care. The Assessing Care Of Vulnerable Elderly (ACOVE) quality indicators (QIs) were developed to assess and improve the care of elderly patients.ObjectivesThe purpose of this review is to summarize studies that assess the quality of care using QIs from or based on ACOVE, in order to evaluate the state of quality of care for the reported conditions.MethodsWe systematically searched MEDLINE, EMBASE and CINAHL for English-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 38 publications
1
49
0
2
Order By: Relevance
“…Our findings are broadly consistent with the findings of a systematic review by Askari et al 13 of 17 papers reporting on achievement of the ACOVE quality indicators, which showed large variation between conditions, and notably low rates for osteoarthritis quality indicators. This review only found a few conditions with a stable pass rate range over multiple studies, and noted that caution is required in making direct comparisons of quality indicator achievement between studies.…”
Section: Quality Indicator Achievementsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are broadly consistent with the findings of a systematic review by Askari et al 13 of 17 papers reporting on achievement of the ACOVE quality indicators, which showed large variation between conditions, and notably low rates for osteoarthritis quality indicators. This review only found a few conditions with a stable pass rate range over multiple studies, and noted that caution is required in making direct comparisons of quality indicator achievement between studies.…”
Section: Quality Indicator Achievementsupporting
confidence: 92%
“…ELSA gathered information on achievement of quality indicators for IHD, hypertension and cerebrovascular disease (CVD) (stroke). A systematic review of 17 quality-of-care papers reporting on the RAND Corporation's Assessing Care of Vulnerable Elders (ACOVE) quality indicators 13 revealed that achievement rates are often high in primary care settings for indicated care for hypertension (72%) and stroke (69%).…”
Section: Cardiovascular Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…10,11 The goal of the American geriatric society revised Beers criteria-2012 was to improve care of elderly patients by reducing their exposure to Potentially inappropriate medications. 12 Early detection of a potentially inappropriate medication can prevent adverse effects. 13 However not all physicians take them into consideration while prescribing to the elderly.…”
Section: Introductionmentioning
confidence: 99%